PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM DESA/KELURAHAN TANGGUH BENCANA (DESTANA) DI KELURAHAN TAMANAN DAN LIRBOYO KECAMATAN MOJOROTO KOTA KEDIRI - Kurniawan, Ficky Adi; Fandayati, Inggit (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2023)
Tamanan Village and Lirboyo Village, located in Mojoroto District, Kediri City are one of the villages affected by flooding, especially when the rainy season arrives. Floods that occur are often caused by problematic drainage and culvert infrastructure. The objective of community empowerment activities through the Tangguh Village Disaster program is to increase the capacity and resilience of the community and village apparatus in Tamanan and Lirboyo Villages in dealing with disasters. The methods used in this study include participatory survey methods, lectures, discussions, exercises/hands-on practice, observation, and evaluation. The results obtained are that a disaster-resilient village/kelurahan has an important role as a buffer for a village affected by a disaster, or becomes an independent village if a disaster occurs.